Students' Self-efficacy in Solving Mathematical Literacy-Based Summative Assessment Problems - Lestari, Dian Endang; Widjajanti, Djamilah Bondan; Susanto, Adi; Hidayati, Kana (Mathematics Education Journal, 2025)
Self-efficacy is an essential skill that students must develop to excel in mathematics. This study aims to describe students' self-efficacy in solving mathematical literacy-based summative assessment problems. Conducted as qualitative descriptive research, the study employed tests and questionnaires for data collection. The sample of this study consisted of 34 male junior high school students. The data obtained were analyzed using descriptive statistical techniques. The results showed that students' self-efficacy was in the medium category with a percentage of 55.88%, and student learning outcomes based on the students’ mathematical literacy-based summative assessment tests were mostly in the poor category with a percentage of 44.11%. The percentages of students who can formulate, use, and interpret mathematical concepts are 78%, 45%, and 59%, respectively. Consequently, students with high levels of self-efficacy outperform those with intermediate or low levels of mathematical literacy. Medium-level individuals demonstrated superior mathematical literacy abilities compared to students with low self-efficacy. Enhancing self-efficacy in addressing mathematical literacy-based summative assessment challenges is crucial for advancing mathematics education research, enabling educators to implement effective pedagogical strategies, and fostering students’ confidence to approach complex problem-solving tasks.